PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), INVESTASI SWASTA, DAN PAJAK DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN BOYOLALI (Tahun 2002 – 2019) - Saputra, Andri; Suharno, Suharno; Widarno, Bambang (Universitas Slamet Riyadi, 2021)
Regional Original Income (ROI) is all regional income derived from theoriginal region's economy. The purpose of this study was to determine the effect ofGross Regional Domestic Product (GRDP), private investment and local taxes onROI. The population in this study is ROI Boyolali Regency, GRDP, privateinvestment and local taxes with annual data for the period 2002–2019. Samplingusing the Nonprobability Sampling method. The data analysis technique used isdescriptive analysis, classical assumption test and hypothesis testing. Theconclusion of the results of this study is that GDP and private investment have nosignificant effect on ROI, while local taxes have a significant effect on ROI.